Toxins of foodborne pathogen Bacillus cereus and the regulatory factors controlling the biosynthesis of its toxins - Yugenraj Navaneethan,; Mohd Esah Effarizah,; Norli Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Bacillus cereus is a versatile organism which causes two distinct types of food poisoning by producing toxins. Toxin formation in B. cereus is very much a complex process involving co-regulation of multiple genes exerting control at transcriptional, translational and post-translational level and such regulations too are often influenced by extrinsic factors. A comprehensive understanding of such factors is very crucial for holistic approaches and strategies in order to minimise food poisoning risk. Hence, this review will focus on the intrinsic and extrinsic factors controlling toxin biosynthesis in B. cereus.